Barriers to Treg therapy in Europe: From production to regulation - Hennessy, Conor; Deptula, Milena; Hester, Joanna; Issa, Fadi (Frontiers in Medicine, 2023)
There has been an increased interest in cell based therapies for a range of medical conditions in the last decade. This explosion in novel therapeutics research has led to the development of legislation specifically focused on cell and gene based therapies. In Europe, the European medicines agency (EMA) designates any medicines for human use which are based on genes, tissues, or cells as advanced therapy medicinal products or ATMPs. In this article we discuss the hurdles to widespread adoption of ATMPs in Europe, with a focus on regulatory T cells (Tregs) There are numerous barriers which must be overcome before mainstream adoption of Treg therapy becomes a reality. The source of the cells, whether to use autologous or allogenic cells, and the methods through which they are isolated and expanded, must all meet strict GMP standards to allow use of the products in humans. GMP compliance is costly, with the equipment and reagents providing a significant cost barrier and requiring specialised facilities and personnel. Conforming to the regulations set centrally by the EMA is difficult, and the different interpretations of the regulations across the various member states further complicates the regulatory approval process. The end products then require a complex and robust distribution network to ensure timely delivery of potentially life saving treatments to patients. In a European market whose logistics networks have been disrupted by covid and Brexit, ensuring rapid and reliable delivery is a more complex task than ever. In this article we will examine the impact of these barriers on the development and adoption of Tregs in Europe, and potential approaches which could facilitate more widespread use of Tregs. Clearer regulation and wider availability of starting materials is ultimately needed to increase the accessibility of Treg development and use. Currently production is concentrated in a few specialised centers, which increases costs and hinders widespread adoption.